Entre documentos e narrativas, a histÃria do Curso de Secretariado Executivo na Universidade Federal do CearÃ, 1985 a 1995 - Ariadina Torres GuimarÃes (2019)
To describe the history and the memory of the creation and implementation of the Executive Secretariat Course of the Federal University of CearÃ from 1985 to 1995 is the main objective of this research. Our specific objectives were: a) To contextualize the scenario lived in CearÃ, from 1985 to 1995; b) Reflect on the memories of the actors involved in the creation and implementation of the course and c) Identify the motivations and expectations of the first students to join and remain in a new course. The research is part of the history of Brazilian education, more specifically the history and memory of higher education in the Executive Secretariat in the State of CearÃ. For this, we use concepts of history and memory. In addition to showing the thinking of the Secretariat area through the paths of secretarial professionals over time, in Brazil and in the World. We use as methodology, as for nature, an applied research; As for the approach to the problem we did a qualitative research; To obtain and collect data we used three procedures: documentary research, bibliographic research and semi-structured interview. The work was divided into four chapters, in addition to the introduction, we have: Chapter II - the memory, the history and the creation of the course of executive secretariat in the UFC; chapter III â the executive secretariat course in Brazil; Chapter IV - creation and implementation of the Executive Secretariat course at the UFC. The first findings lead us to affirm that the course was created by the appeal of society and the protagonism of those involved in the institution.